Replacement Therapy in Patients with Von Willebrand Disease—Indications and Monitoring - Nowak-Göttl, Ulrike; Miesbach, Wolfgang; Koscielny, Jürgen; Dempfle, Carl-Erik; Maegele, Marc; Prondzinski, Mario von Depka; Westrup, Dagmar; Spannagl, Michael (Hämostaseologie, 2019)
In patients with von Willebrand disease (VWD), replacement therapy may be indicated in the case of spontaneous bleeding, surgical interventions and injuries/trauma or as a prophylaxis of spontaneous bleeding episodes. The deficient von Willebrand factor (VWF) is replaced with or without factor VIII (FVIII). Dual VWF/FVIII concentrates can be beneficial in the case of low FVIII level, while repeated dosing may lead to very high FVIII levels, with a potential thrombogenic effect in individual VWD patients. An excessive FVIII:C increase can be limited by using a VWF product with a low level of FVIII, achieving a haemostatic adequate FVIII:C increase after 6 to 12 hours. Replacement therapy in patients with VWD shall be individualised considering VWD type, history and risk of bleeding and risk of thrombosis, as well as indication and the individually variable VWF and FVIII increase. Deviations from the dosages and minimum trough levels mentioned in guidelines or recommendations can be considered in justified cases. The objective of this review is to provide recommendations for specific constellations of replacement therapy based on the VWD-specific guidelines available in Europe, the available evidence, own experiences and the consensus of the interdisciplinary German author group.
Keywords: von Willebrand disease; von Willebrand factor; factor VIII; replacement therapy; bleeding